2021
DOI: 10.21037/atm-21-6653
|View full text |Cite
|
Sign up to set email alerts
|

Lung squamous cell carcinoma with rare epidermal growth factor receptor mutation G719X: a case report and literature review

Abstract: Asians who develop non-small cell lung cancer (NSCLC) have a chance of approximately 50% of harboring the epidermal growth factor receptor (EGFR) mutation. The G719X mutation in EGFR has 3 subtypes (i.e., G719A, G719C, or G719S), all of them being classified as uncommon EGFR mutations.The EGFR mutation G719X is most often associated with lung adenocarcinoma. Conversely, its occurrence in lung squamous cell carcinoma is rare. Its response to tyrosine kinase inhibitor (TKI) treatment remains unknown. A 50-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The patient died 13 months after the surgical resection. Reference: The complex mutation has been previously described in a few reports ( 12 , 13 ). In vitro data suggest that the coexistence of the E709A + G719C mutation confers resistance to adjuvant treatment, including EGFR-TKIs ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…The patient died 13 months after the surgical resection. Reference: The complex mutation has been previously described in a few reports ( 12 , 13 ). In vitro data suggest that the coexistence of the E709A + G719C mutation confers resistance to adjuvant treatment, including EGFR-TKIs ( 14 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent research reported a case of LUSC with an EGFR G719X mutation. The patient underwent EGFR -TKI treatment and achieved an overall survival duration of 25.4 months ( 18 ). Mutations in KRAS and EGFR are usually mutually exclusive, but when coexistent, KRAS mutations may lead to resistance to EGFR inhibitors ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung cancer is the major subtype of lung cancer. Lung squamous cell carcinoma (LUSC) is a most frequent subtype of non-small cell lung cancer and accounts for approximately 40% of diagnosed cases of lung cancer each year (2). Currently, the main treatment strategies for LUSC include surgery, radiotherapy, and chemotherapy (3).…”
Section: Introductionmentioning
confidence: 99%